2018
DOI: 10.3390/ijerph15102245
|View full text |Cite
|
Sign up to set email alerts
|

Applying the WHO International Classification of Functioning, Disability and Health in Nursing Assessment of Population Health

Abstract: Classification systems constitute an important contribution to nursing practice, as they provide standardized frameworks for communication between nurses and other healthcare professionals. International Classification of Functioning, Disability and Health (ICF) provides a unified and standardized language, as well as a working structure, for the description of health and health-related states. This paper aims to describe some of the available classifications used in nursing practice and to identify the potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…This integrative literature review study showed that SNOMED-CT has been being used by nursing in different care contexts, such as the hospital setting, home care, and primary care, aiming to build a standardized language to help the nurses' decision-making in patient care, although still in an incipient way, mainly with regard to scientific studies. In this sense, studies have been carried out to determine its effectiveness and applicability (9,26,30,32) .…”
Section: Journal Of Biomedical Informaticsmentioning
confidence: 99%
See 2 more Smart Citations
“…This integrative literature review study showed that SNOMED-CT has been being used by nursing in different care contexts, such as the hospital setting, home care, and primary care, aiming to build a standardized language to help the nurses' decision-making in patient care, although still in an incipient way, mainly with regard to scientific studies. In this sense, studies have been carried out to determine its effectiveness and applicability (9,26,30,32) .…”
Section: Journal Of Biomedical Informaticsmentioning
confidence: 99%
“…The International Council of Nurses (ICN) considers it essential to use a universal SLS as a strategy for the qualification of nursing services and for the projection of the profession, since the development of a particular vocabulary promotes strengthening of the professional identity, organization of clinical reasoning, and improvement of the practice (8)(9) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The "International Classification of Functioning, Disability and Health" (ICF) is a new health classification system developed by the World Health Organization (WHO) in accordance with the development of health services in countries around the world since 1996. The classification system of disability was promoted worldwide in 2001, and the application of ICF to research, testing, and reporting in the field of health and disability was advocated (1,2). Since the second national sample survey of persons with disabilities in our country in 2006, some of the disability classification indicators in the ICF have been used as a reference, and academic circles have continuously deepened the exploration of ICF, not only applying it in clinical practice, but also in special education and the disabled.…”
Section: Introductionmentioning
confidence: 99%
“…Nurses use a variety of conceptual frameworks to guide data collection from patients that may or may not be discipline-specific (Gómez-Salgado et al, 2018;Munroe et al, 2013Munroe et al, , 2015O'Brien et al 2018).…”
mentioning
confidence: 99%